ANALISIS FAKTOR-FAKTOR RENDAHNYA MINAT BELAJAR MATEMATIKA SISWA DI KELAS X SMK NEGERI 1 ANGKOLA TIMUR - Nasution, Fahmi Ferdiansyah; Ardiana, Nunik; Elindra, Rahmatika (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to: Analyze the factors causing students' low interest in learning in mathematics subjects at East Angkola State Vocational School. The research method used is a survey method with a qualitative approach, where in this research method data is obtained by giving a questionnaire which is then analyzed descriptively. Data analysis was carried out using the Excel computer program. The questionnaire consisted of 20 questions related to 1) feelings of happiness, 2) attention to learning, and 3) interest in the material and teacher, with 4 alternative answers on the questionnaire, namely